Climatological aspects of explosive cyclones in the Mediterranean - Kouroutzoglou, J.a; Flocas, H.A.a; Keay, K.b; Simmonds, I.b; Hatzaki, M.a (International Journal of Climatology, 2011)
An objective climatology of explosive cyclones is performed over a 40-year period (1962-2001), for the Mediterranean region with the aid of the Melbourne University automatic cyclone finding and tracking scheme. The major temporal and spatial characteristics of Mediterranean explosive cyclones are investigated, including frequency, movement, generation and dissipation, scale, depth, and intensity. It was verified that the explosive cyclogenesis in the Mediterranean is a rather rare phenomenon that occurs mainly from November to March. Explosive cyclones preferentially form along the northern Mediterranean coast, with maximum density in the Ligurian and Aegean Seas. The cyclogenesis mechanism that predominates in their development is characterized by an interaction of a short and an open long wave in a pre-existing development (referred to as the KF mechanism). There are distinct differences between Western Mediterranean and Eastern Mediterranean explosive cyclones. Although explosive cyclones tend to form in the Western Mediterranean, their scale and depth is greater in the Eastern Mediterranean. Explosive cyclones more likely move from the main cyclogenetic areas in the Western Mediterranean along specific eastward paths over southern Italy and the Ionian Sea where they dissipate or they generate in Eastern Mediterranean and move north-eastwards to the Black Sea or eastwards to Cyprus and Middle East. © 2010 Royal Meteorological Society.
cited By (since 1996)8
Keywords: Aegean Sea; Black Sea; Climatology; cyclogenesis; cyclone; Cyclonic tracks; Explosives; Ionian Sea; Ligurian Sea; Mediterranean; Mediterranean Region; Mediterranean Sea; Mediterranean Sea (East); Mediterranean Sea (West); Melbourne University tracking algorithm; Meteorological bombs; Metrics; spatial variation; storm track; Storms; temporal variation; vorticity